The Role of Emergency Evacuation Plans in Pro Texting Workers : A Comprehensive Systematic Review - Kevin Chaniago Tanudirjo; Egin Cipta Wiguna; Dendi Handriansyah (The International Journal of Medical Science and Health Research, 2026)
Introduction: Workplace emergencies pose significant risks to worker safety globally. Emergency evacuation plans are critical components of occupational safety, yet their effectiveness in protecting workers varies substantially across settings. This systematic review synthesizes evidence on the role, components, effectiveness, and implementation factors of emergency evacuation plans for worker protection. Methods: A systematic review was conducted following PRISMA guidelines. Eight screening criteria were applied, including worker population focus, emergency evacuation intervention, worker safety outcomes, empirical data, workplace setting, workplace context, evacuation procedures, and worker population focus. Data extraction covered worker populations, evacuation plan types, protective mechanisms, plan components, effectiveness evidence, implementation factors, challenges, and key findings from 80 included studies across diverse industries. Results: Studies spanned healthcare, construction, mining, manufacturing, oil and gas, and other sectors globally. Eight primary plan components were identified: detection/alarm systems, evacuation route design, assembly points, communication protocols, role assignments, training/drills, equipment provision, and emergency services coordination. Integrated multi-component interventions reduced evacuation times by 64% (581 to 212 seconds) and achieved 100% worker survival in severe events. Training improved knowledge by 57-76%, while smart technologies enhanced evacuation efficiency by 35-37%. Critical success factors included regular drills, clear communication, management commitment, and technology integration. Major barriers comprised worker non-compliance (51-70% ignoring instructions), physical obstacles, communication failures, and insufficient training (83.3% demonstrating poor knowledge). Conclusion: Emergency evacuation plans significantly improve worker protection when implemented as integrated systems rather than standalone documents. Effectiveness depends on context-specific tailoring, regular practical training, management commitment, and systematic maintenance. Future efforts should address vulnerable worker populations, technology optimization, and cross-cultural effectiveness. Keywords: Emergency evacuation, worker safety, occupational health, disaster preparedness, systematic review